2011
DOI: 10.1007/s12149-011-0498-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of lung epithelial permeability in the volatile substance abuse using Tc-99m DTPA aerosol scintigraphy

Abstract: Tc-99m DTPA pulmonary clearance is markedly accelerated in the volatile substance abuse. This suggests that inhalant abuse of substance may produce abnormalities in pulmonary alveolo-capillary membrane function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
3
0
1
Order By: Relevance
“…In 2011, Cayir et al . [15] observed that the abuse of volatile drugs increased clearance of 99m Tc-DTPA aerosols, indicating increased pulmonary capillary permeability and damage to the pulmonary capillary endothelium. In 2018, Schniering et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2011, Cayir et al . [15] observed that the abuse of volatile drugs increased clearance of 99m Tc-DTPA aerosols, indicating increased pulmonary capillary permeability and damage to the pulmonary capillary endothelium. In 2018, Schniering et al .…”
Section: Discussionmentioning
confidence: 99%
“…In 2006, Ozşahin et al [14] used a 99m Tc-diethyltriaminepentaacetic acid (DTPA) aerosol scintillation imaging device to observe the permeability of the alveolar basement membrane in patients with type 2 diabetes, whereby increased permeability indicates alveolar basement membrane damage. In 2011, Cayir et al [15] observed that the abuse of volatile drugs increased clearance of 99m Tc-DTPA aerosols, indicating increased pulmonary capillary permeability and damage to the pulmonary capillary endothelium. In 2018, Schniering et al [16] used 177 Lu and 44 Sc to label plasma protein-binding ligands capable of binding albumin (DOTA-PPB-01) and transthyretin (DOTA-PPB-03) to observe nuclear imaging and metabolic distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Einige Kohlenwasserstoffe, wie Trichlorethylen, können eine direkte chemische Pneumonitis
Chemische Pneumonitis
verursachen. Toluolmissbrauch wird mit einem panlobulären Emphysem und dem Goodpasture-Syndrom in Verbindung gebracht [ 47 ]. Häufigere Befunde sind entzündliche Infiltrate
Entzündliches Infiltrat
durch Mikroaspirationen nach Erbrechen.…”
Section: Schnüffelstoffeunclassified
“…, 6 When inhaled, 99m Tc-DTPA particles arrive at the alveolar epithelial surface and then diffuse from the air space into the vascular space. The clearance rate of 99m Tc-DTPA is a reliable index of alveolar epithelial permeability.…”
Section: Introductionmentioning
confidence: 99%